Analisis Pengaruh Persepsi Kemudahan dan Persepsi Manfaat terhadap Penggunaan Financial Technology (Fintech) Mobile pada Bank Syariah Indonesia KCP Muara Bulian - Sumantri Sumantri; Niki Kosasih; Anggun Novita Anggraini (Universitas Batanghari Jambi, 2026)
This study aims to analyze the effect of perceived ease of use and perceived usefulness on the use of Mobile Fintech at Bank Syariah Indonesia (BSI) by applying the Technology Acceptance Model (TAM). A mixed-method approach was employed, combining descriptive qualitative and quantitative analysis. Primary data were obtained from questionnaires distributed to 99 respondents selected through accidental sampling, while secondary data were derived from literature and prior studies. Data were analyzed using validity and reliability tests, multiple regression, t-tests, F-tests, and the coefficient of determination (R²). The results show that perceived ease of use and perceived usefulness have significant positive effects on the use of Mobile Fintech both individually and simultaneously, with a contribution of 77.9% to fintech adoption. These findings are consistent with previous international studies that highlight the importance of ease of use, usefulness, trust, and Shariah compliance in driving Islamic fintech adoption. This study concludes that strengthening user-friendly features, improving system reliability, and ensuring compliance with Islamic principles are essential strategies to enhance the adoption of Mobile Fintech in Islamic banking. This research also contributes theoretically by expanding the application of TAM in the context of Islamic banking, where Shariah compliance and customer trust play a crucial moderating role. The originality of this study lies in combining quantitative findings with contextual challenges in rural Indonesia, which are rarely highlighted in previous research. Furthermore, the practical contribution is to provide a guideline for Islamic banks in formulating digital strategies that align with customer needs, government financial inclusion programs, and technological trends.